2023
DOI: 10.1039/d3ta04418a
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of superconductivity and electride states in Ca2H with an antifluorite-type motif under compression

Qianyi Wang,
Shoutao Zhang,
Honggang Li
et al.

Abstract: An unprecedented hydride Ca2H with an antifluorite-type structure is predicted to possess the coexistence of electride states and superconductivity under pressure. This study paves the way for the search of novel electride superconductor hydrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…CALYPSO 33,34 is a package employing the particle swarm optimization (PSO) algorithm to predict structures, such as clusters, and 3D and 2D materials. 35–37 The ground state structure of the 2D Mg 2 Si monolayer is searched using the CALYPSO package and first-principles calculations. 38 The structural optimization is carried out using the Vienna Ab initio Simulation Package (VASP).…”
Section: Methodsmentioning
confidence: 99%
“…CALYPSO 33,34 is a package employing the particle swarm optimization (PSO) algorithm to predict structures, such as clusters, and 3D and 2D materials. 35–37 The ground state structure of the 2D Mg 2 Si monolayer is searched using the CALYPSO package and first-principles calculations. 38 The structural optimization is carried out using the Vienna Ab initio Simulation Package (VASP).…”
Section: Methodsmentioning
confidence: 99%
“…The crystal structures of SiCN 4 were predicted via the CALYPSO code, which had been demonstrated to be successful in predicting stable structures in many well-known systems. 43–52 The current predictions were performed at 0, 50, 100, 200 and 300 GPa with 1, 2, 3 and 4 chemical formulae, respectively. In each generation, thirty structures were generated and 60% of them were produced using a PSO method.…”
Section: Methodsmentioning
confidence: 99%
“…Recent high-pressure experiments and theoretical calculations on superconductivity like CeH 9 29,30 have shown that high-temperature superconductivity and even room-temperature superconductivity are expected to be realized. There also are a lot of studies 31,32 exploring the dependency of T c with pressure. Some intriguing results on B-rich compounds indicate that low-frequency phonon-mediated superconducting could also generate high T c .…”
Section: Introductionmentioning
confidence: 99%